2009
DOI: 10.2527/jas.2008-0866
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations among carcass cross-sectional fat area ratios, production traits, intramuscular fat, and serum leptin concentration in Duroc pigs

Abstract: Animals accumulate fat in tissues as subcutaneous, intermuscular, intramuscular, and abdominal fat. Genetic interrelationships of respective fat depositions, however, have not been examined in depth. This study estimated genetic parameters for subcutaneous, intermuscular, and abdominal fat areas of 545 Duroc purebred pigs slaughtered at 105 kg of BW. Measurements were obtained using an image analysis system for positions between the 5th and the 6th thoracic vertebra (56TV), at half body length (HBL), and at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 21 publications
(30 reference statements)
4
43
0
Order By: Relevance
“…In another study, image analysis of abdominal fat, INTMF and SQF from adipose tissue samples from Duroc pigs slaughtered at 105 kg indicated that within anatomical sites the genetic correlations between SQ and INTMF were high whereas, correlations between IM and INTMF fat were much lower. 70 Heritability estimates for INTMF varied between locations and were lower than SQF area heritabilities at all three anatomical sites. 70 In finished feed lot steers, heritability estimates for INTMF and SQF were similar (0.40, 0.42).…”
Section: Animal Studies Of Intermuscular Fatmentioning
confidence: 85%
“…In another study, image analysis of abdominal fat, INTMF and SQF from adipose tissue samples from Duroc pigs slaughtered at 105 kg indicated that within anatomical sites the genetic correlations between SQ and INTMF were high whereas, correlations between IM and INTMF fat were much lower. 70 Heritability estimates for INTMF varied between locations and were lower than SQF area heritabilities at all three anatomical sites. 70 In finished feed lot steers, heritability estimates for INTMF and SQF were similar (0.40, 0.42).…”
Section: Animal Studies Of Intermuscular Fatmentioning
confidence: 85%
“…Regarding IMF content it is well known that the occurrence of intramuscular fat deposition has a strong genetic component (Gispert et al, 1997;Suzuki et al, 2009). In this case, the three genotypes of Celta pig showed a markedly different adipogenic capacity, since the Barcina line had more IMF compared to the other ones.…”
Section: Effect Of Genotypementioning
confidence: 92%
“…Lean-line pigs differed in carcase composition from normal pigs, and leptin at slaughter correlated with backfat thickness (r 5 0.73). Suzuki et al (2009) also found leptin correlated with s.c. fat (r . 0.72) and total fat (r .…”
mentioning
confidence: 88%